Mask blank, reflection type mask, and method of producing semiconductor device
By using a mask blank with a thin film of tantalum, niobium, and nitrogen, optimized through X-ray diffraction analysis, the challenges of surface roughness, film stress, and shadowing effects in EUV lithography are addressed, enhancing pattern transfer accuracy and optical properties.
Patent Information
- Application Number
- JP2025019066
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-05-15
AI Technical Summary
In EUV lithography, the shadowing effect caused by obliquely incident EUV light on absorber patterns leads to reduced transfer accuracy of patterns, and thinning the absorber film to mitigate this effect results in high crystallinity and surface roughness, along with significant film stress, which further reduces pattern accuracy and positional accuracy.
A mask blank with a thin film containing tantalum, niobium, and nitrogen, where the X-ray diffraction pattern is analyzed to ensure specific ratios and intensities, reducing surface roughness and film stress, and forming a reflective mask with improved optical properties for EUV light.
The solution achieves a mask blank with low surface roughness and film stress, resulting in improved pattern transfer accuracy and reduced shadowing effects in EUV lithography, while maintaining desired optical properties for the absorber film.
Smart Images

Figure 2025076473000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a mask blank for an exposure mask used in the manufacture of semiconductor devices and the like, a reflective mask which is a reflective exposure mask using this mask blank, and a method for manufacturing semiconductor devices using this reflective mask. [Background technology]
[0002] Exposure equipment used in semiconductor device manufacturing has been evolving while gradually shortening the wavelength of the light source. In order to achieve finer pattern transfer, EUV lithography using extreme ultraviolet light (EUV: Extreme Ultra Violet, hereafter referred to as EUV light) with a wavelength of around 13.5 nm has been developed. In EUV lithography, a reflective mask is used because there are few materials that are transparent to EUV light. Representative reflective masks include the reflective binary mask and the reflective phase shift mask (reflective halftone phase shift mask).
[0003] A reflective binary mask has a relatively thick absorber pattern on top of a highly reflective layer formed on a substrate, which sufficiently absorbs EUV light, whereas a reflective phase shift mask has a relatively thin absorber pattern (phase shift pattern) on top of a highly reflective layer formed on a substrate, which attenuates the EUV light by optical absorption and generates reflected light with a desired phase inversion relative to the reflected light from the highly reflective layer.
[0004] Techniques relating to the above-mentioned reflective mask for EUV lithography and mask blanks for producing the same are described in Patent Documents 1 and 2 below.
[0005] Patent Document 1 describes that the low-reflection portion corresponding to the above-mentioned absorber pattern contains Ta (tantalum) and Nb (niobium), and further contains any one of Si (silicon), O (oxygen) and N (nitrogen). It describes that this low-reflection portion is provided with a lower-layer absorption film and an upper-layer absorption film having low reflectivity and a multilayer structure, and that it is mainly the lower-layer absorption film that has the function of absorbing EUV light, which is the exposure light. Patent Document 1 also describes an example in which a lower-layer absorption film made of Ta and Nb and an upper-layer absorption film made of SiN are formed.
[0006] Patent Document 2 describes that, with regard to the absorbing film constituting the above-mentioned absorber pattern, for an absorbing film containing Ta and nitrogen (N), when the peak diffraction angle 2θ of the peak derived from a tantalum-based material in an X-ray diffraction pattern is 36.8 deg or more and the half-value width of the peak derived from the tantalum-based material is 1.5 deg or more, a sufficient etching rate can be achieved during dry etching treatment. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2010-67757 A [Patent Document 2] JP 2019-35929 A Summary of the Invention [Problem to be solved by the invention]
[0008] In EUV lithography, the exposure light, EUV light, is incident on the reflective mask at an angle. This causes a unique problem called the shadowing effect. The shadowing effect is a phenomenon in which a shadow is cast when the exposure light (EUV light) is incident on an absorber pattern with a three-dimensional structure at an angle, causing changes in the dimensions and position of the transferred pattern. To suppress this shadowing effect, it is necessary to thin the absorber film in the mask blank, which serves as the original for the reflective mask, and thereby thin the absorber pattern.
[0009] However, the absorber film is required to have desired optical characteristics with respect to the exposure light. In particular, in the case of a reflective phase shift mask, it is necessary not only to simply thin the conventional absorber film, but also to reduce both the refractive index [n] and the extinction coefficient [k] of the absorber film with respect to the exposure light (EUV light). In order to achieve such optical characteristics, it is possible to form the absorber film only with metal elements. However, such thin films generally tend to be highly crystalline and have large surface roughness. When an absorber pattern is formed by etching a thin film (absorber film) with high crystallinity and large surface roughness, the edge roughness of the absorber pattern increases. As a result, in EUV lithography using a reflective mask having an absorber pattern, the transfer accuracy of the absorber pattern is greatly reduced. Furthermore, such thin films tend to have large film stress. When an absorber film with large film stress is formed on a substrate, distortion occurs in the substrate. When an absorber pattern is formed by etching an absorber film with large film stress, the absorber pattern moves on the substrate, and the positional accuracy of the absorber pattern is greatly reduced.
[0010] Therefore, an object of the present invention is to provide a mask blank having a thin film for pattern formation in which surface roughness and film stress are suppressed, a reflective mask formed using this mask blank, and a method for manufacturing a semiconductor device using this reflective mask. [Means for solving the problem]
[0011] In order to solve the above problems, the present invention has the following configuration.
[0012] (Configuration 1) A mask blank comprising a multilayer reflective film and a thin film for pattern formation, in this order, on a main surface of a substrate, The thin film is Contains tantalum, niobium, and nitrogen; The X-ray diffraction pattern obtained by analyzing the thin film by out-of-plane measurement of the X-ray diffraction method satisfies at least one of the relationships Imax1 / Iavg1≦7.0 and Imax2 / Iavg2≦1.0, where Imax1 is the maximum value of the diffraction intensity in the diffraction angle 2θ range of 34 degrees to 36 degrees, Iavg1 is the average value of the diffraction intensity in the diffraction angle 2θ range of 32 degrees to 34 degrees, Imax2 is the maximum value of the diffraction intensity in the diffraction angle 2θ range of 40 degrees to 42 degrees, and Iavg2 is the average value of the diffraction intensity in the diffraction angle 2θ range of 38 degrees to 40 degrees. Mask blank.
[0013] (Configuration 2) The thin film has a maximum diffraction intensity at a diffraction angle 2θ of 38 degrees or less in the range of a diffraction angle 2θ of 30 degrees or more and 50 degrees or less in the X-ray diffraction pattern. 2. The mask blank according to claim 1.
[0014] (Configuration 3) The ratio of the niobium content [atomic %] to the total content [atomic %] of tantalum and niobium in the thin film is less than 0.6. 3. The mask blank according to configuration 1 or 2.
[0015] (Configuration 4) The nitrogen content of the thin film is 30 atomic % or less. 4. A mask blank according to any one of claims 1 to 3.
[0016] (Configuration 5) The total content of tantalum, niobium, and nitrogen in the thin film is 95 atomic % or more. 5. A mask blank according to any one of configurations 1 to 4.
[0017] (Configuration 6) The thin film contains boron. 5. A mask blank according to any one of configurations 1 to 4.
[0018] (Configuration 7) The total content of tantalum, niobium, boron, and nitrogen in the thin film is 95 atomic % or more. 7. The mask blank according to claim 6.
[0019] (Configuration 8) The refractive index of the thin film at extreme ultraviolet wavelengths is 0.95 or less. 8. A mask blank according to any one of configurations 1 to 7.
[0020] (Configuration 9) The extinction coefficient of the thin film at the wavelength of extreme ultraviolet light is 0.03 or less. 9. A mask blank according to any one of configurations 1 to 8.
[0021] (Configuration 10) A reflective mask comprising a multilayer reflective film and a thin film having a transfer pattern formed thereon, in this order, on a main surface of a substrate, the thin film comprises tantalum, niobium, and nitrogen; The X-ray diffraction pattern obtained by analyzing the thin film by out-of-plane measurement of the X-ray diffraction method satisfies at least one of the relationships Imax1 / Iavg1≦7.0 and Imax2 / Iavg2≦1.0, where Imax1 is the maximum value of the diffraction intensity in the diffraction angle 2θ range of 34 degrees to 36 degrees, Iavg1 is the average value of the diffraction intensity in the diffraction angle 2θ range of 32 degrees to 34 degrees, Imax2 is the maximum value of the diffraction intensity in the diffraction angle 2θ range of 40 degrees to 42 degrees, and Iavg2 is the average value of the diffraction intensity in the diffraction angle 2θ range of 38 degrees to 40 degrees. Reflective mask.
[0022] (Configuration 11) The thin film has a maximum diffraction intensity at a diffraction angle 2θ of 38 degrees or less in the range of a diffraction angle 2θ of 30 degrees or more and 50 degrees or less in the X-ray diffraction pattern. 11. The reflective mask according to configuration 10.
[0023] (Configuration 12) The ratio of the niobium content [atomic %] to the total content [atomic %] of tantalum and niobium in the thin film is less than 0.6. 12. A reflective mask according to configuration 10 or 11.
[0024] (Configuration 13) The nitrogen content of the thin film is 30 atomic % or less. 13. A reflective mask according to any one of configurations 10 to 12.
[0025] (Configuration 14) The total content of tantalum, niobium, and nitrogen in the thin film is 95 atomic % or more. 14. A reflective mask according to any one of configurations 10 to 13.
[0026] (Configuration 15) The thin film contains boron. 14. A reflective mask according to any one of configurations 10 to 13.
[0027] (Configuration 16) The total content of tantalum, niobium, boron, and nitrogen in the thin film is 95 atomic % or more. 16. The reflective mask according to claim 15.
[0028] (Configuration 17) The refractive index of the thin film at extreme ultraviolet wavelengths is 0.95 or less. 17. A reflective mask according to any one of configurations 10 to 16.
[0029] (Configuration 18) The extinction coefficient of the thin film at the wavelength of extreme ultraviolet light is 0.03 or less. A reflective mask according to any one of configurations 10 to 17.
[0030] (Configuration 19) 19. A method for manufacturing a semiconductor device comprising the steps of: exposing and transferring a transfer pattern to a resist film on a semiconductor substrate using the reflective mask according to any one of configurations 10 to 18. A method for manufacturing a semiconductor device. Effect of the Invention
[0031] According to the present invention, it is possible to provide a mask blank having a thin film for pattern formation with low surface roughness and low film stress, a reflective mask formed using this mask blank, and a method for manufacturing a semiconductor device using this reflective mask. [Brief description of the drawings]
[0032] [Figure 1] 1 is a cross-sectional view showing a configuration of a mask blank according to an embodiment of the present invention. [Diagram 2] 1 is a cross-sectional view showing a configuration of a reflective mask according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a diagram showing an X-ray diffraction pattern for explaining the physical properties of a thin film of a mask blank according to an embodiment of the present invention. [Figure 4] 1 is a graph (part 1) showing the relationship between the composition of a tantalum (Ta)-niobium (Nb)-based material and the surface roughness and film stress. [Diagram 5] 2 is a graph (part 2) showing the relationship between the composition of a tantalum (Ta)-niobium (Nb)-based material and the surface roughness and film stress. [Figure 6] Graph (part 3) showing the relationship between the composition of a tantalum (Ta)-niobium (Nb)-based material and the surface roughness and film stress. [Figure 7] 1A to 1C are manufacturing process diagrams showing a method for manufacturing a reflective mask according to the present invention. [Figure 8] FIG. 2 is a diagram showing the conditions for forming thin films in Examples and Comparative Examples, and the physical properties and compositions of the formed thin films. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] Hereinafter, the embodiments of the present invention will be described, but first, the background to the invention will be described. The inventors first considered using a material containing niobium (Nb) in tantalum (Ta) as a thin film for absorbing EUV light in a mask blank for a reflective mask. However, a thin film formed from such a material has high crystallinity, and it was difficult to make the film have an amorphous quality, preferably a microcrystalline quality, as required for a thin film for absorbing EUV light in a mask blank.
[0034] Therefore, the present inventors attempted to reduce both the crystallinity (surface roughness) and film stress of a thin film for EUV light absorption containing tantalum (Ta) and niobium (Nb) by further containing nitrogen (N). However, when the tendency of surface roughness and film stress for the composition (content of each) of tantalum (Ta), niobium (Nb) and nitrogen (N) in a thin film was investigated, it was found that the correlation was not high, and it was difficult to reduce the surface roughness and film stress of the film by using this composition as an index. The reason for this is presumed to be that the thin film for pattern formation in a mask blank is formed by a sputtering method, but in the film formation by the sputtering method, the environment in the film formation chamber (flow rate of sputtering gas, sputtering gas pressure, etc.) has a large effect on the crystallinity and film stress of the formed thin film.
[0035] However, even if the environment in the deposition chamber is specified so that the surface roughness and film stress of the thin film are in the suitable range, the parameters are specific to the deposition apparatus used for the deposition, and the same characteristics may not be obtained when applied to other deposition apparatuses. Furthermore, there is a problem that it requires a lot of effort to measure the surface roughness and film stress of each deposited thin film.
[0036] Therefore, the inventors of the present invention have further studied these problems. As a result, they have found that the X-ray diffraction pattern obtained by measuring a thin film using the X-ray diffraction method is an index of the surface roughness and film stress of the thin film, as described below. The X-ray pattern is a graph showing the X-ray intensity [CPS] for each diffraction angle 2θ [deg], and is defined here as the X-ray diffraction pattern obtained when an analysis is performed using out-of-plane measurement.
[0037] First, we focused on the maximum peak intensity occurring near the diffraction angle 2θ position (34-36[deg] and 40-42[deg]) corresponding to tetraniobium trinitride (Nb4N3) in the X-ray diffraction pattern obtained for the thin film for EUV light absorption. However, X-ray diffraction intensity is easily variable depending on the measurement conditions, and it is difficult to use it as an index as it is. Therefore, as a result of further investigation, we came to the idea that it would be better to use the ratio obtained by dividing the maximum peak intensity [Imax] occurring near the diffraction angle 2θ position corresponding to tetraniobium trinitride (Nb4N3) by the average value [Iavg] of each X-ray intensity [CPS] in the diffraction angle 2θ[deg] region where the influence of the peak corresponding to tetraniobium trinitride (Nb4N3) is relatively small as an index.
[0038] There are two ratios used as the above index. The first ratio is the ratio [Imax1 / Iavg1] obtained by dividing the maximum peak intensity [Imax1] in the range (34-36[deg]) near the position of the diffraction angle 2θ corresponding to tetraniobium trinitride (Nb4N3) by the average intensity [Iavg1] in the range of 32-34[deg]. The second ratio is the ratio [Imax2 / Iavg2] obtained by dividing the maximum peak intensity [Imax2] in the range (40-42[deg]) near the position of the diffraction angle 2θ corresponding to tetraniobium trinitride (Nb4N3) by the average intensity [Iavg2] in the range of 38-40[deg]. These two ratios are used independently, and at least one of them may be used as an index, and both may be used as indexes.
[0039] When the relationship between the above two ratios obtained from the X-ray diffraction pattern of the thin film and the surface roughness and film stress of the thin film was investigated, it was found that the first ratio [Imax1 / Iavg1] is preferably 7.0 or less, and the second ratio [Imax2 / Iavg2] is preferably 1.0 or less. Furthermore, it was found that the thin film does not need to satisfy both the conditions of the two ratios [Imax1 / Iavg1] and [Imax2 / Iavg2] in the X-ray diffraction pattern, and that if either one of them is satisfied, both the surface roughness and film stress of the thin film can be sufficiently reduced.
[0040] Here, the above-mentioned sufficiently reduced surface roughness means, for example, a root mean square roughness [Sq] of less than 0.3 [nm]. The root mean square roughness (hereinafter referred to as surface roughness [Sq]) is a value measured by an atomic force microscope (AFM) in a rectangular region with one side of 1 [μm] as a measurement region. The film stress is a deformation amount (substrate warpage amount) of the substrate caused by forming the thin film of 200 [nm] or less. The deformation amount of the substrate is expressed by calculating the difference shape between the surface shape of the thin film and the surface shape of the substrate before the thin film is formed, and expressing the difference shape as the difference between the maximum height and the minimum height in a rectangular region with one side of 142 [mm] based on the center of the substrate. The root mean square roughness [Sq] is a parameter for evaluating surface roughness defined in ISO25178, and is an extension of the line roughness parameter [Rq] (root mean square roughness of line) that represents two-dimensional surface properties defined in ISO4287 and JIS B0601 up until now to three dimensions (surface). The calculation formula is shown as the following formula (1).
[0041]
number
[0042] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. Note that the following embodiment is one form for embodying the present invention, and does not limit the scope of the present invention. In addition, in the drawings, the same or corresponding parts are given the same reference numerals, and the description thereof may be simplified or omitted.
[0043] <Mask blanks and reflective masks> Fig. 1 is a cross-sectional view showing the configuration of a mask blank 100 according to an embodiment of the present invention. The mask blank 100 shown in this figure is an original of a reflective mask for EUV lithography using EUV light as exposure light. Fig. 2 is a cross-sectional view showing the configuration of a reflective mask 200 according to an embodiment of the present invention, which is manufactured by processing the mask blank 100 shown in Fig. 1. The configurations of the mask blank 100 and the reflective mask 200 according to the embodiment will be described below with reference to Figs. 1 and 2.
[0044] 1 has a substrate 1, and a multilayer reflective film 2, a protective film 3, and a thin film 4, which are laminated in this order from the substrate 1 side on one main surface 1a of the substrate 1. The thin film 4 is a film on which a transfer pattern is formed by processing. The mask blank 100 may also have an etching mask film 5 provided on the thin film 4 as necessary. This mask blank 100 has a conductive film 10 on the other main surface of the substrate 1 (hereinafter referred to as back surface 1b).
[0045] 2 is obtained by patterning the thin film 4 in the mask blank 100 shown in Fig. 1 as a transfer pattern 4a. Details of each part constituting the mask blank 100 and the reflective mask 200 will be described below with reference to Figs. 1 and 2.
[0046] <Substrate 1> The substrate 1 is preferably one having a low thermal expansion coefficient within the range of 0±5 ppb / °C in order to prevent distortion of the transfer pattern 4a due to heat generation during exposure to EUV light (EUV exposure) using the reflective mask 200. Materials having a low thermal expansion coefficient within this range include, for example, SiO2-TiO2 glass and multi-component glass ceramics. The transfer pattern 4a is a pattern formed by processing the thin film 4 as described above.
[0047] The main surface 1a of the substrate 1 is surface-processed to have a high degree of flatness in order to obtain pattern transfer accuracy and positional accuracy in EUV exposure using the reflective mask 200. In the case of EUV exposure, the flatness in a 132 mm×132 mm area of the main surface 1a of the substrate 1 is preferably 0.1 μm or less, more preferably 0.05 μm or less, and particularly preferably 0.03 μm or less.
[0048] The back surface 1b of the substrate 1 is the surface that is electrostatically chucked when the reflective mask 200 is set in the exposure tool, and in an area of 132 mm×132 mm, the flatness is preferably 0.1 μm or less, more preferably 0.05 μm or less, and particularly preferably 0.03 μm or less. Note that the back surface 1b of the mask blank 100 in an area of 142 mm×142 mm has a flatness of preferably 1 μm or less, more preferably 0.5 μm or less, and particularly preferably 0.3 μm or less.
[0049] In addition, the surface smoothness of the substrate 1 is also an extremely important item. The surface roughness of the main surface 1a of the substrate 1 is preferably 0.1 nm or less in terms of root-mean-square roughness [Sq]. The surface smoothness can be measured by an atomic force microscope.
[0050] Furthermore, the substrate 1 preferably has high rigidity in order to suppress deformation due to film stress of the films formed on the main surface 1a and the back surface 1b. In particular, the substrate 1 preferably has a high Young's modulus of 65 GPa or more.
[0051] <Multilayer reflective film 2> The multilayer reflective film 2 is formed on the main surface 1a and reflects the EUV light, which is the exposure light, with high reflectance. This multilayer reflective film 2 imparts the function of reflecting EUV light to the reflective mask 200 formed using this mask blank 100, and is a multilayer film in which layers containing elements with different refractive indices as main components are periodically laminated.
[0052] Generally, a multilayer film in which a thin film (high refractive index layer) of a light element or its compound, which is a high refractive index material, and a thin film (low refractive index layer) of a heavy element or its compound, which is a low refractive index material, are alternately stacked for about 40 to 60 periods, is used as the multilayer reflective film 2. The multilayer film may be stacked multiple times, with a high refractive index layer / low refractive index layer stacked in this order from the substrate 1 side as one period. The multilayer film may also be stacked multiple times, with a low refractive index layer / high refractive index layer stacked in this order from the substrate 1 side as one period. Note that the top layer of the multilayer reflective film 2, that is, the surface layer of the multilayer reflective film 2 on the opposite side to the substrate 1, is preferably a high refractive index layer. In the above-mentioned multilayer film, when a high refractive index layer / low refractive index layer stacked in this order from the substrate 1 is stacked multiple times, with a high refractive index layer / low refractive index layer stacked in this order as one period, the top layer is a low refractive index layer. In this case, if the low refractive index layer constitutes the top surface of the multilayer reflective film 2, it is easily oxidized, and the reflectance of the reflective mask 200 decreases. For this reason, it is preferable to further form a high refractive index layer on the uppermost low refractive index layer to form the multilayer reflective film 2. On the other hand, in the above-mentioned multilayer film, when a laminate structure of low refractive index layer / high refractive index layer in which a low refractive index layer and a high refractive index layer are laminated in this order from the substrate 1 side is one period, the uppermost layer is the high refractive index layer and may be left as it is.
[0053] In this embodiment, a layer containing silicon (Si) is used as the high refractive index layer. In addition to simple Si, a Si compound containing boron (B), carbon (C), nitrogen (N), and oxygen (O) in addition to Si can be used as the material containing Si. By using a layer containing Si as the high refractive index layer, a reflective mask 200 for EUV lithography with excellent reflectance of EUV light can be obtained. In this embodiment, a glass substrate is preferably used as the substrate 1. Si also has excellent adhesion to the glass substrate. As the low refractive index layer, a simple metal selected from molybdenum (Mo), ruthenium (Ru), rhodium (Rh), and platinum (Pt), or an alloy thereof is used. For example, as the multilayer reflective film 2 for EUV light with a wavelength of 13 nm to 14 nm, a Mo / Si periodic laminate film in which Mo films and Si films are alternately laminated for about 40 to 60 periods is preferably used. The high refractive index layer, which is the top layer of the multilayer reflective film 2, may be formed of silicon (Si).
[0054] The reflectance of the multilayer reflective film 2 alone is usually 65% or more, with the upper limit usually being 73%. The thickness and period of each constituent layer of the multilayer reflective film 2 may be appropriately selected according to the exposure wavelength, and are selected so as to satisfy the law of Bragg reflection. The multilayer reflective film 2 has a plurality of high refractive index layers and a plurality of low refractive index layers, but the thicknesses of the high refractive index layers and the low refractive index layers do not have to be the same. The thickness of the outermost Si layer of the multilayer reflective film 2 can be adjusted within a range that does not reduce the reflectance. The thickness of the outermost Si layer (high refractive index layer) can be in the range of 3 nm to 10 nm.
[0055] The method of forming the multilayer reflective film 2 is known in the art. For example, the multilayer reflective film 2 can be formed by depositing each layer by ion beam sputtering. In the case of the Mo / Si periodic multilayer film described above, a Si film having a thickness of about 4.2 nm is first deposited on the substrate 1 by using a Si target by ion beam sputtering. Then, a Mo film having a thickness of about 2.8 nm is deposited by using a Mo target. This Si film / Mo film is regarded as one period, and 40 to 60 periods are laminated to form the multilayer reflective film 2 (the top layer is a Si layer). For example, when the multilayer reflective film 2 is formed into 60 periods, the number of steps increases compared to 40 periods, but the reflectance for EUV light can be increased. In addition, when forming the multilayer reflective film 2, it is preferable to form the multilayer reflective film 2 by supplying krypton (Kr) ion particles from an ion source and performing ion beam sputtering.
[0056] <Protective film 3> The protective film 3 is a film provided to protect the multilayer reflective film 2 from etching and cleaning when the mask blank 100 is processed to manufacture a reflective mask 200 for EUV lithography. The protective film 3 is provided on the multilayer reflective film 2, either in contact with the multilayer reflective film 2 or via another film. The protective film 3 also serves to protect the multilayer reflective film 2 when a black defect in the transfer pattern 4a in the reflective mask 200 is repaired using an electron beam (EB).
[0057] 1 and 2 show the case where the protective film 3 is a single layer, but the protective film 3 may have a laminated structure of two or more layers. The protective film 3 is made of a material that is resistant to an etchant and a cleaning solution used when patterning the thin film 4. By forming the protective film 3 on the multilayer reflective film 2, damage to the surface of the multilayer reflective film 2 can be suppressed when a reflective mask 200 is manufactured using a substrate 1 having the multilayer reflective film 2 and the protective film 3. Therefore, the reflectance characteristic of the multilayer reflective film 2 to EUV light is improved.
[0058] In the following, an example will be described in which the protective film 3 is a single layer. When the protective film 3 includes multiple layers, the properties of the material of the uppermost layer of the protective film 3 (the layer in contact with the thin film 4) become important in relation to the thin film 4.
[0059] In the mask blank 100 of this embodiment, a material that is resistant to the etching gas used in the dry etching for patterning the thin film 4 formed on the protective film 3 can be selected as the material of the protective film 3.
[0060] The protective film 3 preferably contains ruthenium (Ru). The material of the protective film 3 may be a simple Ru metal, or a Ru alloy containing at least one metal selected from ruthenium (Ru), titanium (Ti), niobium (Nb), molybdenum (Mo), zirconium (Zr), yttrium (Y), rhodium (Rh), boron (B), lanthanum (La), cobalt (Co), and rhenium (Re), and may contain nitrogen. On the other hand, the protective film 3 may use a material selected from silicon-based materials such as silicon (Si), a material containing silicon (Si) and oxygen (O), a material containing silicon (Si) and nitrogen (N), and a material containing silicon (Si), oxygen (O) and nitrogen (N).
[0061] In EUV lithography, there are few substances transparent to the EUV light, which is the exposure light. Therefore, it is technically difficult to arrange a dust mask (EUV pellicle) that prevents foreign matter from adhering to the surface of the reflective mask 200 on which the transfer pattern 4a is formed. For this reason, pellicle-less operation without a dust mask has become mainstream. Also, in EUV lithography, exposure contamination occurs, such as the deposition of a carbon film or the growth of an oxide film on the reflective mask 200 due to EUV exposure. Therefore, when the reflective mask 200 is used in the manufacture of semiconductor devices, it is necessary to frequently clean the mask to remove foreign matter and contamination on the mask. For this reason, the reflective mask 200 is required to have a mask cleaning resistance that is orders of magnitude higher than that of a transmission mask for normal optical lithography, and the reflective mask 200 has the protective film 3, which makes it possible to increase the cleaning resistance against cleaning liquid.
[0062] The thickness of the protective film 3 is not particularly limited as long as it can function to protect the multilayer reflective film 2. From the viewpoint of the reflectance of EUV light, the thickness of the protective film 3 is preferably 1.0 nm or more and 8.0 nm or less, more preferably 1.5 nm or more and 6.0 nm or less.
[0063] The method for forming the protective film 3 may be any known film forming method without any particular limitations. Specific examples include various sputtering methods, such as DC sputtering, RF sputtering, and ion beam sputtering, as well as atomic layer deposition (ALD).
[0064] <Thin film 4 and transfer pattern 4a> The thin film 4 is a film used as an absorber film that absorbs EUV light, and serves as a film for forming a transfer pattern 4a of a reflective mask 200 configured using this mask blank 100. The transfer pattern 4a is formed by patterning this thin film 4. In this embodiment, the thin film 4 of such a mask blank 100 contains at least tantalum (Ta), niobium (Nb), and nitrogen (N). Furthermore, this thin film 4 is a tantalum (Ta)-niobium (Nb)-based material that contains at least nitrogen (N), and may contain, for example, boron (B) as other materials.
[0065] It is preferable that such a thin film 4 has a microcrystalline or amorphous crystal structure, and as will be shown in the examples below, it has been found that the inclusion of nitrogen (N) in a tantalum (Ta)-niobium (Nb)-based material reduces the crystallinity of the thin film 4. However, since the degree of reduction in crystallinity has little correlation with the composition of tantalum (Ta), niobium (Nb), and nitrogen (N) in the thin film, the thin film 4 is defined by its X-ray diffraction pattern.
[0066] That is, the thin film 4 has an X-ray diffraction pattern obtained by out-of-plane measurement of an X-ray diffraction method that satisfies at least one of the following physical properties (a) and (b). Fig. 3 is a diagram showing an X-ray diffraction pattern for explaining the physical properties of the thin film of the mask blank according to the embodiment of the present invention. Hereinafter, the physical properties (a) and (b) relating to X-ray diffraction possessed by the thin film 4 will be explained with reference to Fig. 3.
[0067] (a) In the X-ray diffraction pattern, when the maximum value of the diffraction intensity in the range [A1] of the diffraction angle 2θ between 34 degrees and 36 degrees is [Imax1] and the average value of the diffraction intensity in the range [A2] of the diffraction angle 2θ between 32 degrees and 34 degrees is [Iavg1], ([Imax1] / [Iavg1]) is ≦ 7.0. The range [A1] is the range in the vicinity of the position of the diffraction angle 2θ corresponding to tetraniobium trinitride (Nb4N3). The range [A2] is the range of the diffraction angle 2θ [deg] in which the influence of the peak corresponding to tetraniobium trinitride (Nb4N3) is relatively small.
[0068] (b) When the maximum value of the diffraction intensity in the range [A3] of the diffraction angle 2θ in the X-ray diffraction pattern of 40 degrees or more and 42 degrees or less is [Imax2], and the average value of the diffraction intensity in the range [A4] of the diffraction angle 2θ in the range of 38 degrees or more and 40 degrees or less is [Iavg2], ([Imax2] / [Iavg2]) is ≦ 1.0. The range [A3] is the range in the vicinity of the position of the diffraction angle 2θ corresponding to tetraniobium trinitride (Nb4N3). The range [A4] is the range of the diffraction angle 2θ [deg] in which the influence of the peak corresponding to tetraniobium trinitride (Nb4N3) is relatively small.
[0069] In addition, in the thin film 4, within the range of the diffraction angle 2θ of 30 degrees or more and 50 degrees or less in the X-ray diffraction pattern, it is preferable that the diffraction intensity be maximum when the diffraction angle 2θ is in the range of 38 degrees or less.
[0070] The thin film 4 as described above is formed by a sputtering method, and by adjusting the environment in the film formation chamber (such as the flow rate of the sputtering gas and the sputtering gas pressure), it satisfies at least one of the physical properties (a) and (b) related to the X-ray diffraction described above.
[0071] Moreover, the thin film 4 having the above physical properties related to X-ray diffraction has a small surface roughness and a small film stress, as will be described in the following examples. Specifically, the thin film 4 has a surface roughness [Sq] (root mean square roughness) of less than 0.3 [nm] when the film thickness is about 50 nm. This root mean square roughness [Sq] is a value measured by an atomic force microscope (AFM) in a rectangular region with a side of 1 [μm] for a thin film formed on a test substrate. The film stress of the thin film 4 is such that the deformation of the test substrate caused by forming the thin film 4 is 200 [nm] or less. The deformation of the test substrate is expressed by calculating the difference between the surface shape of the thin film 4 and the surface shape of the test substrate before the thin film 4 is formed, and expressing the difference between the maximum height and the minimum height in the inner region of a rectangle with a side of 142 [mm] based on the center of the test substrate. The test substrate was made of SiO2-TiO2 type glass similar to the substrate 1 of the mask blank 100, and had a 6025 size (approximately 152 mm x 152 mm x 6.35 mm) with both main surfaces polished.
[0072] In addition, since the thin film 4 having the above-mentioned physical properties related to X-ray diffraction has low crystallinity, i.e., is a microcrystalline or amorphous film, the transfer pattern 4a of the reflective mask 200 obtained by patterning this thin film 4 is a pattern with reduced edge roughness. Furthermore, as described above, the transfer pattern 4a of the reflective mask 200 obtained by patterning the thin film 4 with low film stress is a pattern with good formation position accuracy. As a result, it is possible to improve the transfer accuracy of the pattern in EUV lithography using this reflective mask 200.
[0073] Here, Figs. 4 to 6 are graphs (part 1) to (part 3) showing the relationship between the composition of tantalum (Ta)-niobium (Nb)-based materials and the surface roughness and film stress. Fig. 4 is a graph related to a thin film made of tantalum (Ta)-niobium (Nb), and Figs. 5 and 6 are graphs related to a thin film made of tantalum (Ta)-niobium (Nb) containing nitrogen (N). In each graph, the horizontal axis indicates the composition of the thin film, the left vertical axis indicates the surface roughness [Sq] (root mean square roughness), and the right vertical axis indicates the above-mentioned film stress. Note that, in each thin film, the composition ratio was adjusted by changing the composition and flow rate of the gas used for film formation in sputtering film formation using a target having the composition ratio of tantalum (Ta):niobium (Nb) shown in each graph. Each thin film has a film thickness of 50 nm. The composition ratio of each thin film is the average value of the composition ratio analyzed in the depth direction by X-ray photoelectron spectroscopy (XPS) after film formation.
[0074] As can be seen from Figures 4 to 6, thin films made of tantalum (Ta)-niobium (Nb)-based materials have a low correlation between the composition and the surface roughness or film stress, making it difficult to reduce the surface roughness and film stress of the film using the composition as an indicator.
[0075] In addition, the thin film 4 having either of the above-mentioned X-ray diffraction properties (a) or (b) has a ratio of the niobium (Nb) content [atomic %] to the total content [atomic %] of tantalum (Ta) and niobium (Nb) of less than 0.6, as described in the following examples. Furthermore, the nitrogen (N) content of the thin film 4 is 30 atomic % or less. And the total content of tantalum (Ta), niobium (Nb), and nitrogen (N) in the thin film 4 is 95 atomic % or more. Furthermore, when the thin film 4 contains boron (B), the total content of tantalum (Ta), niobium (Nb), nitrogen (N), and boron (B) in the thin film 4 is 95 atomic % or more.
[0076] The thin film 4 having the above composition has a low refractive index [n] and low extinction coefficient [k]. It can also be seen that the extinction coefficient [k] of tantalum (Ta)-niobium (Nb)-based materials (TaNbN, TaNbBN) containing nitrogen (N) tends to decrease as the niobium (Nb) content increases.
[0077] For example, the thin film 4 having the above-mentioned physical properties and composition ranges related to X-ray diffraction has a refractive index [n] of 0.95 or less at the wavelength of EUV light. Furthermore, the thin film 4 has an extinction coefficient [k] of 0.03 or less at the wavelength of EUV light. Such a thin film 4 is used as a phase shift film, and when the transfer pattern 4a of the reflective mask 200 is a phase shift pattern, the film thickness can be set in a thinner range. Therefore, when the reflective mask 200 is a phase shift mask, the transfer pattern 4a, which is a phase shift pattern, is made thinner, and the shadowing effect of the reflective mask 200 can be suppressed.
[0078] Here, the film thickness of the thin film 4 used as the phase shift film is adjusted so as to have the following reflectance. That is, when the transfer pattern 4a of the reflective mask 200 is a phase shift pattern, the thin film 4 is configured as a phase shift film. Such a thin film 4 absorbs EUV light while reflecting a part of the EUV light at a level that does not adversely affect the pattern transfer. Also, in the portion of the reflective mask 200 where the transfer pattern 4a is to be formed, the protective film 3 is exposed at the opening where the thin film 4 has been removed. Therefore, the EUV light irradiated to the reflective mask 200 is reflected by the surface of the thin film 4 and the multilayer reflective film 2 via the protective film 3 exposed from the thin film 4.
[0079] When the transfer pattern 4a is a phase shift pattern, the material and thickness of the thin film 4 are set so that a desired phase difference is obtained between the reflected light of the EUV light on the surface of the thin film 4 and the reflected light of the EUV light on the opening where the thin film 4 has been removed. This phase difference is about 130 degrees to 230 degrees, and the reflected lights with inverted phase differences of about 180 degrees or about 220 degrees interfere with each other at the pattern edge, improving the image contrast of the projected optical image. With this improvement in image contrast, the resolution increases, and various tolerances related to exposure, such as exposure dose tolerance and focus tolerance, are expanded.
[0080] In order to obtain such a phase shift effect, the relative reflectance of the surface of the thin film 4 to EUV light is preferably 2% to 40%, more preferably 6% to 35%, even more preferably 15% to 35%, and particularly preferably 15% to 25%, although this depends on the pattern and exposure conditions. Here, the relative reflectance of the transfer pattern 4a refers to the reflectance of the EUV light reflected from the thin film 4 when the reflectance of the EUV light reflected from a portion without the thin film 4 is taken as 100%.
[0081] Although it depends on the pattern and exposure conditions, in order to obtain a phase shift effect, the absolute reflectance of the thin film 4 (or the transfer pattern 4a which becomes the phase shift pattern) to EUV light is preferably 4% to 27%, and more preferably 10% to 17%, and the film thickness is set so as to obtain such absolute reflectance.
[0082] Moreover, the thin film 4 as described above can also be used as an absorber film for a binary mask by adjusting the film thickness.
[0083] <Etching mask film 5> The etching mask film 5 is a layer provided on the thin film 4 in the mask blank 100 or in contact with the surface of the thin film 4, and serves as a mask pattern when the thin film 4 is patterned. This etching mask film 5 is a layer that has been removed and is not present in the reflective mask 200.
[0084] The material of the etching mask film 5 is one that provides a high etching selectivity of the thin film 4 to the etching mask film 5. Here, the "etching selectivity of B to A" refers to the ratio of the etching rates of A, which is a layer that does not need to be etched (a layer that serves as a mask), and B, which is a layer that needs to be etched. Specifically, it is specified by the formula "etching selectivity of B to A=etching rate of B / etching rate of A". In addition, "high selectivity" refers to a selectivity value, as defined above, that is high relative to a comparative object. The etching selectivity of the thin film 4 to the etching mask film 5 is preferably 1.5 or more, and more preferably 3 or more.
[0085] The thin film 4 formed of a material containing at least tantalum (Ta), niobium (Nb), and nitrogen (N) in this embodiment can be etched by dry etching using a chlorine-based gas. In dry etching using a chlorine-based gas as an etchant, a material containing chromium (Cr) can be exemplified as a material having a high etching selectivity with respect to the thin film 4 formed of a Ta-Nb-based material containing N. Specific examples of materials containing chromium (Cr) include materials containing chromium and one or more elements selected from nitrogen, oxygen, carbon, and boron, etc. Examples include CrN, CrON, CrCN, CrCON, CrBN, CrBON, CrBCN, and CrBOCN. These materials may contain metals other than chromium within the range in which the effects of the present invention can be obtained. The method for forming such an etching mask film 5 can be, for example, by magnetron sputtering or ion beam sputtering using a chromium (Cr) target.
[0086] The thickness of the etching mask film 5 is desirably 2 nm or more from the viewpoint of obtaining the function as an etching mask for accurately forming a transfer pattern on the thin film 4. Moreover, the thickness of the etching mask film 5 is desirably 15 nm or less from the viewpoint of reducing the thickness of the resist film formed on the etching mask film 5 when the mask blank 100 is processed to manufacture the reflective mask 200.
[0087] <Conductive film 10> The conductive film 10 is a film for attaching the reflective mask 200 to an exposure device by electrostatic chuck. The electrical characteristics (sheet resistance) required for such a conductive film 10 for electrostatic chucks are usually 100 Ω / □ (Ω / Square) or less. The conductive film 10 can be formed, for example, by magnetron sputtering or ion beam sputtering using targets of metals and alloys such as chromium (Cr) and tantalum (Ta).
[0088] The chromium (Cr)-containing material of the conductive film 10 is preferably a Cr compound that contains Cr and further contains at least one selected from boron (B), nitrogen (N), oxygen (O), and carbon (C).
[0089] The material containing tantalum (Ta) for the conductive film 10 is preferably Ta, an alloy containing Ta, or a Ta compound containing any of these and at least one of boron, nitrogen, oxygen, and carbon.
[0090] The thickness of the conductive film 10 is not particularly limited as long as it satisfies the function for electrostatic chuck. The thickness of the conductive film 10 is usually 10 nm to 200 nm. The conductive film 10 also functions to adjust the stress on the back surface 1b side of the mask blank 100. That is, the conductive film 10 is adjusted to obtain a flat mask blank 100 and a flat reflective mask 200 by balancing the stress from various films formed on the main surface 1a side.
[0091] <Method of manufacturing reflective mask> Fig. 7 is a manufacturing process diagram showing a method for manufacturing a reflective mask of the present invention, illustrating the procedure for manufacturing the reflective mask 200 shown in Fig. 2 using the mask blank 100 shown in Fig. 1. The method for manufacturing a reflective mask will be described below with reference to Fig. 7.
[0092] First, as shown in Fig. 7(1), a mask blank 100 is prepared. This mask blank 100 is the mask blank 100 described with reference to Fig. 1, and is, for example, a mask blank 100 having an etching mask film 5 formed on a thin film 4. However, if the mask blank 100 does not have the etching mask film 5, the etching mask film 5 is formed on the thin film 4. Thereafter, a resist film 20 is formed on the etching mask film 5 by, for example, spin coating. Note that the mask blank 100 may be provided with the resist film 20, in which case the step of forming the resist film 20 is not necessary.
[0093] 7B, the resist film 20 is subjected to a lithography process to form a resist pattern 20a by patterning the resist film 20. In this lithography process, for example, exposure by electron beam lithography, a development process, and a rinsing process are performed.
[0094] 7(3), the etching mask film 5 is etched using the resist pattern 20a as a mask to form an etching mask pattern 5a. Thereafter, the resist pattern 20a is removed by ashing or with a resist remover.
[0095] Next, as shown in Fig. 7(4), the thin film 4 is etched using the etching mask pattern 5a as a mask to form a transfer pattern 4a. At this time, since the constituent material of the thin film 4 is a tantalum (Ta)-niobium (Nb)-based material containing at least nitrogen (N), etching is performed using a chlorine-based gas containing oxygen or a chlorine-based gas as an etching gas. In this etching, the protective film 3 made of a material containing ruthenium (Ru) or silicon oxide (SiO2) acts as an etching stopper to prevent etching damage from being applied to the multilayer reflective film 2, and since the protective film 3 itself has etching resistance, no surface roughness is generated.
[0096] After the above, the etching mask pattern 5a is removed to obtain the reflective mask 200 shown in Fig. 2. The etching mask pattern 5a is removed by wet cleaning using an acidic or alkaline aqueous solution. Even during this wet cleaning, the protective film 3 prevents the multilayer reflective film 2 from being damaged.
[0097] The transfer pattern 4a of the reflective mask 200 obtained as described above is formed by etching the thin film 4 with small surface roughness and film stress, so that the sidewall roughness is suppressed to be small and the shape accuracy and position accuracy are good. The thin film 4 constituting the transfer pattern 4a is a film with a small refractive index [n] and extinction coefficient [k]. Therefore, when the transfer pattern 4a is used as a phase shift pattern, the film thickness of the transfer pattern 4a can be reduced, resulting in a reflective phase shift mask capable of suppressing the occurrence of the shadowing effect.
[0098] <Method for manufacturing semiconductor devices> The method for manufacturing a semiconductor device according to the present invention is characterized in that the above-described reflective mask 200 is used to expose and transfer a transfer pattern 4a of the reflective mask 200 to a resist film on a substrate. Such a method for manufacturing a semiconductor device is carried out as follows.
[0099] First, a substrate on which a semiconductor device is to be formed is prepared. This substrate may be, for example, a semiconductor substrate, a substrate having a semiconductor thin film, or a substrate having a fine patterned film formed thereon. A resist film is formed on the prepared substrate, and pattern exposure is performed on this resist film using the reflective mask 200 of the present invention, and the transfer pattern 4a formed on the reflective mask 200 is exposed and transferred onto the resist film. In this case, EUV light is used as the exposure light.
[0100] After the above steps, the resist film onto which the transfer pattern 4a has been exposed and transferred is developed to form a resist pattern, and then the surface layer of the substrate is etched or impurities are introduced using the resist pattern as a mask. After the processing is completed, the resist pattern is removed.
[0101] By carrying out the above-mentioned processes and further carrying out necessary processing, a semiconductor device is completed.
[0102] In the manufacture of the semiconductor device as described above, a resist pattern with an accuracy that fully satisfies the initial design specifications can be formed on a substrate by performing pattern exposure using EUV light as exposure light using a reflective mask 200 having a transfer pattern 4a with good shape accuracy. In addition, if the reflective mask 200 is a reflective phase shift mask, the occurrence of the shadowing effect is suppressed, and a resist pattern with good shape accuracy and position accuracy can be formed. As described above, when a circuit pattern is formed by dry etching the underlying film using the pattern of this resist film as a mask, a high-precision circuit pattern without wiring short circuits or breaks due to insufficient accuracy can be formed. EXAMPLES
[0103] Next, Examples 1-4 to which the present invention is applied and Comparative Examples 1-3 thereof will be described. Fig. 8 is a diagram showing the conditions for forming the thin film on the mask blank of the Examples and Comparative Examples, and the physical properties and composition of the formed thin film. Below, Examples 1-4 and Comparative Examples 1-3 will be described with reference to Figs. 1 and 8 above.
[0104] <Mask blank formation> <Example 1-3> The mask blank 100 of Example 1-3 was produced as follows. First, a SiO2-TiO2-based glass substrate, which was a low thermal expansion glass substrate having a 6025 size (approximately 152 mm x 152 mm x 6.35 mm) with both main surfaces polished, was prepared as the substrate 1. In order to make both main surfaces of the substrate 1 flat and smooth, polishing was performed using a rough polishing process, a precision polishing process, a localized polishing process, and a touch polishing process.
[0105] Next, one of the main surfaces of the substrate 1 was designated as the back surface 1b, and a conductive film 10 made of a CrN film was formed on the back surface 1b by magnetron sputtering (reactive sputtering). The conductive film 10 was formed to a thickness of 20 nm using a Cr target in a mixed gas atmosphere of argon (Ar) gas and nitrogen (N2) gas.
[0106] Next, the side opposite to the back surface 1b on which the conductive film 10 is formed is set as the main surface 1a of the substrate 1, and the multilayer reflective film 2 is formed on this main surface 1a. The multilayer reflective film 2 formed on the substrate 1 is a periodic multilayer reflective film made of molybdenum (Mo) and silicon (Si) in order to make the multilayer reflective film 2 suitable for EUV light with a wavelength of 13.5 nm. The multilayer reflective film 2 is formed by alternately laminating Mo layers and Si layers on the substrate 1 by ion beam sputtering in a krypton (Kr) gas atmosphere using a Mo target and a Si target. First, a Si film is formed with a thickness of 4.2 nm, and then a Mo film is formed with a thickness of 2.8 nm. This is set as one period, and 40 periods are laminated in the same manner, and finally a Si film is formed with a thickness of 4.0 nm to form the multilayer reflective film 2.
[0107] Subsequently, a protective film 3 made of a SiO2 film was formed on the surface of the multilayer reflective film 2 by RF sputtering using a SiO2 target in an Ar gas atmosphere to a thickness of 2.6 nm.
[0108] Next, a film (TaNbN film) containing tantalum (Ta), niobium (Nb), and nitrogen (N) was formed as thin film 4 by DC magnetron sputtering. At this time, a sputtering target having a target ratio (atomic percentage ratio) of tantalum (Ta):niobium (Nb) shown in FIG. 8 was used, and thin film 4 was formed to a thickness of 50 nm in a film formation gas atmosphere of xenon gas (Xe) and nitrogen gas (N2). The gas flow rate and gas pressure during film formation are as shown in FIG. 8.
[0109] <Example 4> The mask blank 100 was produced in the same manner as in the production procedure of the mask blank 100 of Example 1-3, except that a film containing boron (B) (TaNbBN film) was further formed in the formation of the thin film 4 in the production procedure of the mask blank 100 of Example 1-3. In this case, the thin film 4 was formed in a film formation gas atmosphere of xenon gas (Xe) and nitrogen gas (N2) by co-sputtering using two targets, a mixed target of tantalum (Ta):boron (B) (Ta:B=4:1 atomic % ratio) and a niobium (Nb) target, to a thickness of 50 nm. The gas flow rate and gas pressure during film formation are as shown in FIG. 8.
[0110] <Comparative Example 1> A mask blank was produced in the same manner as the mask blank 100 of Example 1-3, except that a film (TaNb film) containing tantalum (Ta) and niobium (Nb) without nitrogen (N) was formed in the formation of the thin film 4 in the production procedure of the mask blank 100 of Example 1-3. At this time, a sputtering target having a target ratio of tantalum (Ta):niobium (Nb) shown in Fig. 8 was used to form a thin film to a thickness of 50 nm in a film formation gas atmosphere of xenon gas (Xe). The gas flow rate and gas pressure during film formation are as shown in Fig. 8.
[0111] <Comparative Example 2-3> In the formation of the thin film 4 in the manufacturing procedure of the mask blank 100 of Examples 1-3, a film containing tantalum (Ta), niobium (Nb), and nitrogen (TaNbN film) was formed by changing the gas flow rates of xenon gas (Xe) and nitrogen gas (N2) as shown in FIG. 8, and a mask blank was manufactured in the same procedure as the manufacturing procedure of the mask blank 100 of Examples 1-3 except for this. The gas flow rate and gas pressure during film formation are as shown in FIG. 8.
[0112] ≪Evaluation of the thin films in each mask blank≫ The thin films of the mask blanks manufactured in Examples 1-4 and Comparative Examples 1-3 were directly formed on a substrate, and the physical properties and compositions of the formed thin films of Examples 1-4 and Comparative Examples 1-3 were evaluated. As the substrate, the same substrate as the substrate used for manufacturing the mask blank was used.
[0113] <Physical properties related to X-ray diffraction> For each of the thin films of Examples 1-4 and Comparative Examples 1-3, an X-ray diffraction pattern was measured by performing an analysis by Out-of-Plane measurement of the X-ray diffraction method. The results are shown in FIG. 3. Also, based on the X-ray diffraction patterns of Examples 1-4 and Comparative Examples 1-3 shown in FIG. 3, the physical properties (a) and (b) related to X-ray diffraction of each thin film were calculated. The results are shown in accordance with FIG. 8. Note that the X-ray diffraction patterns of Examples 1-4 and Comparative Examples 1-3 shown in FIG. 3 have the reference value (origin) of the diffraction intensity (Intensity) changed so that the differences between the X-ray diffraction patterns can be easily compared even if they are described in one graph. The actual measured values such as Imax are the numerical values described in FIG. 8.
[0114] As shown in Figs. 3 and 8, the thin films of Examples 1 and 2 were confirmed to be films (TaNbN films) containing nitrogen (N), tantalum (Ta), and niobium (Nb) from the deposition material, and to satisfy both the conditions of physical properties (a) and (b) related to X-ray diffraction, and to be the thin film 4 constituting the mask blank of the present invention. Similarly, the thin film of Example 3 was confirmed to be a TaNbN film, and to satisfy the condition of physical property (b) related to X-ray diffraction, and to be the thin film 4 constituting the mask blank of the present invention. Furthermore, the thin film of Example 4 was confirmed to be a film (TaNbBN film) containing boron (B), nitrogen (N), tantalum (Ta), and niobium (Nb) from the deposition material, and to satisfy both the conditions of physical properties (a) and (b) related to X-ray diffraction, and to be the thin film 4 constituting the mask blank of the present invention.
[0115] On the other hand, the thin film of Comparative Example 1 is a film that satisfies both conditions (a) and (b) of physical properties related to X-ray diffraction, but is a tantalum (Ta)-niobium (Nb)-based film (TaNb film) that does not contain nitrogen (N) in the film formation material, and does not correspond to the thin film 4 constituting the mask blank of the present invention.
[0116] Furthermore, the thin films of Comparative Examples 2 and 3 are films (TaNbN films) containing nitrogen (N), tantalum (Ta), and niobium (Nb) from the film-forming materials, but since they do not satisfy any of the conditions for the physical properties (a) and (b) related to X-ray diffraction, it was confirmed that they do not correspond to the thin film 4 constituting the mask blank of the present invention.
[0117] <Surface roughness and film stress> The surface roughness and film stress of each thin film of Examples 1-4 and Comparative Examples 1-3 were measured. The results are also shown in FIG. 8. The surface roughness [Sq] (root mean square roughness) was measured by AFM in a rectangular region with a side of 1 μm as described above. The film stress was expressed as the difference between the surface shape of the thin film and the surface shape of the substrate before the thin film was formed, and the difference between the maximum height and the minimum height (amount of substrate warpage) in the inner region of a rectangle with a side of 142 mm, based on the center of the substrate, of the difference shape. The surface shapes were measured using a surface shape measuring device UltraFLAT200M (manufactured by Corning TROPEL).
[0118] As shown in Fig. 8, the surface roughness [Sq] (root mean square roughness) of each thin film of Examples 1-4 was suppressed to less than 0.3 [nm], and the film stress (amount of substrate warpage) was suppressed to 200 [nm] or less. In contrast, the surface roughness [sq] of each thin film of Comparative Example 1-3 exceeded 0.3 [nm], and the film stress (amount of substrate warpage) exceeded 200 [nm].
[0119] As a result of the above, it was confirmed that by applying the present invention, a mask blank having a thin film for pattern formation in which surface roughness and film stress are suppressed to low levels can be obtained.
[0120] <Refractive index and extinction coefficient> The refractive index [n] and extinction coefficient [k] for EUV light (wavelength 13.5 nm) were measured for each of the thin films of Examples 1, 2, and Comparative Example 2, which are representative of Examples 1 to 4 and Comparative Examples 1 to 3. The results are also shown in FIG.
[0121] As shown in Fig. 8, both the thin film 4 of Example 1 and the thin film of Comparative Example 2 had a refractive index [n] of 0.95 or less and an extinction coefficient [k] of 0.03 or less. As a result, when a reflective mask is formed using the thin film 4 of Example 1 as a phase shift pattern, the film thickness of the phase shift pattern of the reflective mask can be set in a thinner range. As a result, when the reflective mask 200 is a phase shift mask, it was confirmed that the transfer pattern 4a, which is the phase shift pattern, is made thinner, and the effect of suppressing the occurrence of the shadowing effect of the reflective mask 200 can be obtained.
[0122] <Cleaning resistance and etching rate> The cleaning resistance and etching rate of each thin film in Examples 1-4 were measured. The cleaning resistance was measured as the amount of film loss (SPM film loss) of the thin film 4 when the thin film 4 was exposed to a sulfuric acid-hydrogen peroxide aqueous solution (SPM cleaning solution) used as a cleaning solution for mask blanks and reflective masks. The etching rate was measured as the etching speed of the thin film when the thin film 4 was exposed to a chlorine gas (Cl2) atmosphere used as an etchant for the thin film 4 when processing a mask blank to create a reflective mask. The results are also shown in FIG. 8.
[0123] 8, the amount of SPM film loss was small, within 0.015 (nm / min), for each thin film in Examples 1-4, confirming that the thin films had sufficient SPM resistance. Furthermore, the etching rate was confirmed to be sufficiently fast, at 1.30 (nm / sec) or higher, for each thin film in Examples 1-4.
[0124] <Thin film composition> The composition ratios of the thin films of Examples 1 to 4 and Comparative Example 2, which is representative of Comparative Examples 1 to 3, were analyzed in the depth direction by XPS. The results are also shown in FIG.
[0125] As shown in FIG. 8, the thin film of Example 1-4 was confirmed to have a ratio of the niobium (Nb) content [atomic %] to the total content [atomic %] of tantalum (Ta) and niobium (Nb) of less than 0.6. Furthermore, the nitrogen (N) content was confirmed to be 30 atomic % or less. Furthermore, the thin film of Example 1-3 was confirmed to be a film containing tantalum (Ta), niobium (Nb), and nitrogen (N), and the total content thereof was confirmed to be 95 atomic % or more. In contrast, the thin film of Comparative Example 2 was confirmed to have a ratio of the niobium (Nb) content [atomic %] to the total content [atomic %] of tantalum (Ta) and niobium (Nb) of less than 0.6, but the nitrogen (N) content was 30 atomic % or more.
[0126] On the other hand, based on the above film formation conditions, the thin film of Example 4 can be said to be a film substantially composed of tantalum (Ta), niobium (Nb), nitrogen (N), and boron (B), and the total content of these elements can be said to be 95 atomic % or more. [Explanation of symbols]
[0127] 1...Substrate 1a…Main surface 2…Multilayer reflective film 3...Protective film (other films) 4. Thin film 4a…Transfer pattern 100 mask blanks 200 Reflective mask
Claims
1. A mask blank comprising a multilayer reflective film and a thin film for pattern formation, in this order, on a main surface of a substrate, The thin film is containing tantalum, niobium, and nitrogen, the nitrogen content being 30 atomic % or less; The thin film has a maximum diffraction intensity at a diffraction angle 2θ of 38 degrees or less in a range of a diffraction angle 2θ of 30 degrees or more and 50 degrees or less in an X-ray diffraction pattern obtained by performing an analysis by out-of-plane measurement of an X-ray diffraction method. Mask blank.
2. The thin film has a maximum value of the diffraction intensity when the diffraction angle 2θ is 36 degrees or more and 38 degrees or less. The mask blank according to claim 1 .
3. The ratio of the nitrogen content [atomic %] to the total content [atomic %] of tantalum and niobium in the thin film is 0.289 or less. The mask blank according to claim 1 or 2.
4. The ratio of the niobium content [atomic %] to the total content [atomic %] of tantalum and niobium in the thin film is less than 0.
6. The mask blank according to claim 1 .
5. The total content of tantalum, niobium, and nitrogen in the thin film is 95 atomic % or more. The mask blank according to claim 1 .
6. The thin film contains boron. The mask blank according to claim 1 .
7. The total content of tantalum, niobium, boron, and nitrogen in the thin film is 95 atomic % or more. The mask blank according to claim 6.
8. The refractive index of the thin film at the wavelength of extreme ultraviolet light is 0.95 or less. The mask blank according to claim 1 .
9. The extinction coefficient of the thin film at the wavelength of extreme ultraviolet light is 0.03 or less. The mask blank according to claim 1 .
10. A transfer pattern is formed on the thin film in the mask blank according to any one of claims 1 to 9. Reflective mask.
11. The method includes a step of exposing and transferring a transfer pattern onto a resist film on a semiconductor substrate using the reflective mask according to claim 10. A method for manufacturing a semiconductor device.
Citation Information
Patent Citations
Reflection type mask blank for EUV lithography
JP2021174003A
Reflective mask blank, method for manufacturing reflective mask blank, reflective mask, and method for manufacturing semiconductor device
WO2015030159A1
Substrate provided with electroconductive film, substrate provided with multi-layer reflective film, reflective mask blank, reflective mask, and method for manufacturing semiconductor device
WO2016204051A1
Halftone-type EUV mask, halftone-type EUV mask blank, production method of halftone-type EUV mask, and pattern transfer method
JP2010067757A
Reflection type mask blank and reflection type mask
JP2019035929A